2021
DOI: 10.1080/23144599.2021.1989937
|View full text |Cite
|
Sign up to set email alerts
|

Migratory birds as a potential overseas transmitter of Shiga toxin-producing Escherichia coli

Abstract: Shiga toxin-producing Escherichia coli (STEC) has a great public health importance. This study was conducted to investigate the potential role of migratory birds in the transmission of STEC. For this purpose, cloacal swabs were collected from 349 migratory birds (209 ducks and 140 quails) from Damietta governorate, Egypt. The collected swabs were cultured for isolation of STEC using the STEC CHROMagar. STEC isolates were identified based on colonial characteristics, Gram’s stain, convent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…However, the distribution of these genes differs significantly among bird species; for the stx gene, the prevalence rate ranges from 91% in ravens up to 3% in songbirds, and for the eae gene, from 93% in hawks up to 4.6% in geese. Interestingly, the studies performed by Seleem et al [ 162 ] covering the phylogenetic analysis of the obtained stx genes revealed high genetic relatedness to those isolated from human cases in countries where such birds either lived or which were in their migratory pathway. In conclusion, the study underlines the potential role of migratory birds in spreading STEC across their migratory path.…”
Section: Virulence Profiles and Genetic Diversity Of Bacteria Isolate...mentioning
confidence: 99%
“…However, the distribution of these genes differs significantly among bird species; for the stx gene, the prevalence rate ranges from 91% in ravens up to 3% in songbirds, and for the eae gene, from 93% in hawks up to 4.6% in geese. Interestingly, the studies performed by Seleem et al [ 162 ] covering the phylogenetic analysis of the obtained stx genes revealed high genetic relatedness to those isolated from human cases in countries where such birds either lived or which were in their migratory pathway. In conclusion, the study underlines the potential role of migratory birds in spreading STEC across their migratory path.…”
Section: Virulence Profiles and Genetic Diversity Of Bacteria Isolate...mentioning
confidence: 99%
“…Wild birds were first identified as a source of STEC in 1997 ( Wallace et al, 1997 ), in which, 1–3% of bacterial isolates recovered from fecal samples of wild birds were STEC O157:H7. Ever since, diverse STEC strains have been detected and isolated from various bird species including pet birds worldwide ( Kobayashi et al, 2002 , 2009 ; Neher et al, 2016 ; Sanches et al, 2017 ; Navarro-Gonzalez et al, 2020 ; Seleem et al, 2021 ). Birds could disseminate STEC into environments and/or transmit STEC to other animals including humans directly or indirectly.…”
Section: Introductionmentioning
confidence: 99%